Analisis Profitabilitas Usaha Kerupuk Amplang dengan Sistem Penjualan Langsung dan Tidak Langsung di Kecamatan Pemangkat, Kabupaten Sambas - Nirawati Nirawati; Dewi Merdekawati; Maryono Maryono; Muslimah Muslimah; Indra Mahyudi S (Journal of Fisheries and Marine Applied Science, 2026)
Amplang cracker production is a fish-processing activity with the potential to increase value added and improve the income of coastal communities. Differences in sales systems may affect business costs, revenue, income, efficiency, and profitability. This study aimed to analyze the costs, revenue, income, efficiency, and profitability of amplang cracker businesses using direct and indirect sales systems and to compare the profitability of the two systems in Pemangkat District, Sambas Regency. A quantitative approach with a descriptive-comparative method was employed. The study involved 13 business owners selected through saturated sampling. Primary data were collected through observation, interviews, and questionnaires and were analyzed using total cost, revenue, income, R/C ratio, and profitability calculations. The results showed that the direct sales system generated a total monthly cost of IDR 14,657,466, revenue of IDR 19,306,317, income of IDR 4,648,852, an R/C ratio of 1.32, and profitability of 31.70%. The indirect sales system generated a total monthly cost of IDR 16,754,812, revenue of IDR 21,386,965, income of IDR 4,632,154, an R/C ratio of 1.28, and profitability of 27.60%. Both sales systems were efficient and profitable. Descriptively, the direct sales system achieved higher efficiency and profitability, whereas the indirect sales system generated a higher sales volume and revenue.